Power and Law in The Context of Separation of Powers: A Qualitative Study of The Relationship Between The Executive and The Judiciary - Amirudin, Dede; Christian, Christian; Nurseha, Samsudin; Al-aytami, Abdul Musyfiq (International Journal of Social Service and Research, 2024)
This study aims to delve deeper into the relationship between the executive and the judiciary in the context of separation of powers. Through a qualitative study approach, this study will analyze the dynamics of power and the role of law in influencing the interaction between the two branches of government. The research will involve in-depth interviews with legal practitioners, judges, executive officers, and other relevant stakeholders to gather in-depth qualitative data. Data analysis will be carried out by taking into account theoretical perspectives and concepts related to separation of powers, political power, judicial independence, and the role of law in the government system. The results of this study conclude that a better understanding of the dynamics of power and law in the relationship between the executive and the judiciary provides valuable insights for policymakers and law enforcers in strengthening the separation of powers and improving equitable governance systems.